Survivor tree - Colleen, Marcie (Little, Brown and Company, 2021)
The Callery pear tree standing at the base of the World Trade Center is almost destroyed on September 11, but it is pulled from the rubble, coaxed back to life, and replanted as part of the 9/11 memorial.